Solo leveling. 11 - Ch'ugong (Chugong. Solo leveling, 2024)
After saving Jinho from the vengeful Dongsoo Hwang, Jinwoo makes a public declaration that he will protect his family and friends no matter what. But when a close ally is killed in a sudden attack by the otherworldly Monarchs, Jinwoo is forced to reexamine who it is he wants to protect-and just how far he'll go to do so.